Філософсько-історичні трактування поняття «історичний наратив» - Ліщук-Торчинська, Тетяна Петрівна; Lishchuk-Torchynska, Tetiana P. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Постульовано зв’язок історії як історіографічного тексту з наративною репрезентацією минулого. Наголо-шено на полемічній спрямованості в розкритті Ф. Анкерсмітом і П. Рікером змісту історичного наративу. Основний зміст трактування історичного наративу Ф. Анкерсмітом, П. Рікером, Й. Рюзеном проаналізовано у зв’язку з теоретичними основами їхніх учень. A content of interpretations of historical narrative were analyzed by F. Ankersmit, P. Ricoeur and J. Rusen. Was accented, that F. Ankersmit chose the term of «ideal narrative» as a means of interpretation. On conclusion, that in the theory of F. Ankersmit fundamental importance has interpretative component of the historical text and the language of narrative of historian. It was noted that P. Ricoeur interprets the story in the historiography on the basis of the concept of «event-history». Highlighted selection by P. Ricoeur, after L. O. Mink, attribute of the integrality and the need of understand in the narrative. P. Ricoeur’s idea about the importance of understanding the Other in the comprehension of the past, focusing on the quality of temporality in the historical narrative and design features of the story were accented. Heuristic potential of typology of historical proposed by J. Rusen and layers of narrative allocated to them was defined.
Philosophical and Historical Interpretation of the Concept of «Historical Narrative»
Keywords: історичний наратив; historical narrative; Ф. Анкерсміт; F. Ankersmit; П. Рікер; P. Ricoeur; Й. Рюзен; J. Rusen; наративна мова; narrative language; подієва історія; event history; типології історичного; typology of historical